Vertical Gardens as Swamp Coolers. (2015) - Davis, M.J.M.; Ramírez, F.; Vallejo, A.L.
Abstract: This paper explores the potential of a vertical garden to function as a swamp cooler, passing an airflow through the substrate, in much the same way as in a direct evaporative cooler. The 2011 ASHRAE handbook[1]provides guidance on the use of evaporative coolers. They are presented as a low energy contender for air conditioning systems in hot, dry climates. The most basic and direct evaporative coolers (a.k.a. swamp coolers) work by converting sensible heat in the air into latent heat, by passing air through a saturated pad (i.e. the energy required to evaporate water into the air). The concept presented here is that a vertical garden can act as a swamp cooler. This concept is based on the research by Davis & Ramirez[2] on vertical gardens. Davis & Ramirez[2] found that a vertical garden had the potential to act as a swamp cooler. However, there were complications in quantifying the effectiveness of the cooling, due to a suspected pre-heating of the incoming airflow because of glass fronting to the vertical garden. This paper sets out to build on Davis & Ramirez's work, where the experiment is replicated without the glass fronting and where improved measurements of temperatures and relative humidity levels are taken. Thus, a more reliable efficiency is determined for a vertical garden as a swamp cooler.